2021
DOI: 10.1111/ctr.14387
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cardiopulmonary exercise test after heart transplantation

Abstract: Background:The clinical utility of cardiopulmonary exercise testing (CPET) has not been extensively studied yet in heart transplantation (HTX) patients. Objective:To analyze the predictive value of the CPET on hospitalizations and mortality in HTX recipients.Methods: A retrospective cohort was performed from a secondary database.Patients > 18 years with HTX who underwent a CPET between 3 and 12 months after transplantation were included. Time to the first primary endpoint (HTX-related hospitalization) was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Aerobic exercise training pre-HT can have beneficial effects for patients awaiting HT in order to maintain fitness and reduce complications from surgery (10). In addition, CR programs subsequent to HT have been demonstrated to improve exercise aerobic capacity for HT recipients (11)(12)(13)(14)(15)(16)(17). Research studies that have included exercise training continuing beyond traditional CR have demonstrated that high-intensity exercise training is very beneficial (18)(19)(20)(21)(22)(23)(24)(25)(26) and may elicit more benefits when compared with moderate-intensity exercise training (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic exercise training pre-HT can have beneficial effects for patients awaiting HT in order to maintain fitness and reduce complications from surgery (10). In addition, CR programs subsequent to HT have been demonstrated to improve exercise aerobic capacity for HT recipients (11)(12)(13)(14)(15)(16)(17). Research studies that have included exercise training continuing beyond traditional CR have demonstrated that high-intensity exercise training is very beneficial (18)(19)(20)(21)(22)(23)(24)(25)(26) and may elicit more benefits when compared with moderate-intensity exercise training (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, regular assessments of physical fitness (endurance capacity and muscle strength) are needed to adjust the duration and/or intensity of the exercise sessions [ 154 ]. CPET can be advised after 6 weeks (useful in individualized ET for phases III–IV of CR) in the first 3–6 months of intervention (before the reinnervation and development of HR variability) and then at least once per year to estimate the dynamic of physical capacity, while 6-min walking tests and 1-RM tests can be executed more often (e.g., every 2 weeks) while hospital admission or check-ups in the outpatient department [ 2 , 37 , 107 , 157 , 158 ]. The end-goal should remain HIT, if tolerated by the patient, with periods of 85%–95% of maximum HR.…”
Section: Rehabilitation After Heart Transplantationmentioning
confidence: 99%
“…Although more research is still needed in different aspects of the field, newer studies have addressed both long-term effects of HIT [ 108 , 160 ], possible mechanisms for the “HIT effect” [ 109 ], comparison of exercise modalities [ 110 , 157 ], HIT in de novo HTx recipients [ 111 ], and demonstrated stronger evidence of reinnervation [ 161 ].…”
Section: Rehabilitation After Heart Transplantationmentioning
confidence: 99%
“…Several studies have been inconclusive regarding the prognostic value to MET after cardiac transplantation [ 148 , 149 , 150 ]. Iglesias et al identified pVO2, oxygen pulse, and percent predicted pVO2 as being independently associated with hospitalizations after cardiac transplantation [ 151 ].…”
Section: Metabolic Exercise Test In Patients With Heart Failurementioning
confidence: 99%